Mapping Hans Christian Andersen’s A Visit to Portugal: lived and fictional spaces - Pascoal, Sara (Aktualitet - Litteratur, kultur og medier, 2019)
This article intends to undertake a multifocal interpretation of Hans Christian Andersen’s 1866 travelogue about his journey to Portugal, entitled A Visit to Portugal. Based on a quantitative survey of the place names mentioned and a qualitative study of the described landscape characteristics this article maps the lived space (firstspace) intersected with the fictionalized space (secondspace), to enhance what Edward Soja calls the thirdspace, a space where “(…) everything comes together… subjectivity and objectivity, the abstract and the concrete, the real and the imagined, the knowable and the unimaginable, the repetitive and the differential, structure and agency, mind and body, consciousness and the unconscious, the disciplined and the transdisciplinary, everyday life and unending history.” (Soja, 1996, p. 56).